The Determinants and Prevalence of Drug Abuse by Gender in the Selected Competitive Sports at the Universities in Kenya - Ramara, Timothy; Munayi , Simon; Bailasha, Nicholas; Janet, Janet (American Journal of Recreation and Sports, 2023)
Purpose: The main objective of this study was to identify the determinants and prevalence of drug abuse by gender in selected competitive sports at the universities in Kenya. Methodology: The study used a mixed methods research design with an intention to capture and utilise both qualitative andquantitative data. The study sample comprised 300 respondents. Out of the 300 students, 173(57.7%) were male and 127 (42.3%) were female players derived from six selected competitive sports at the universities in Kenya.The selected sports were badminton, tennis, basketball, volleyball, soccer and rugby. Stratified sampling followed by simple random sampling was used to select 10 universities proportionately (4 private and 6 public), the method was the most appropriate to capture universities with women rugby in addition to the five other selected sports. The study sought to investigate the prevalence of drug abuse due to factors such as psychosocial, medicinal and competition. SPSS computer version 20 was used to process data. The data was presented inform of Tables. Findings: The study found that more male players than females abused drugs, with majority being rugby players. Findings indicated that there were more males than females abusing drugs at approximately 89% and 11% respectively. It was concluded that more male than female athletes engaging in sports in universities in Kenya, abuse drugs. This could be attributed to the assumption that males tend to experiment more on most things than do their female counterparts. Unique Contribution to Theory, Practice and Policy: The Social Learning Theory, Self Determination Theory and Harm Reduction Theory may be used to anchor future studies. It was recommended that various stakeholders that include the university management, NACADA and the security apparatus work together with an aim to sensitize and curb drug abuse menace among university athletes, general students' community and the entire community bordering the universities.